Interlingual idiomaticity and cross-cultural communication (English-Ukrainian correspondences) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The paper examines interlingual idiomatic correspondences in English and Ukrainian as specific mental forms predetermined by cultural, ethnic and linguistic factors. It studies the cases of isomorphism and anisomorphism of the contrasted idioms.
Keywords: interlingual idiomaticity; interlingual correspondences; isomorphism and anisomorphism